The multidimensional g-fraction with nonequivalent variables corresponding to the formal multiple power series - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2009)
In this paper we consider the multidimensional g-fraction with nonequivalent variables which is the generalization of the continued g-fraction. The correspondence between the formal multiple power series and the above mentioned fraction is studied.